Study Of Non Point Source Heavy Metal Cadmium Level In Mangrove Plant Sediment At Likupang: Addressed To The Conservation Of The Bunaken National Park - James Jobert Hanoch Paulus; Desy M. H. Mantiri; Rene Ch. Kepel; Natalie D. C. Rumampuk; Fransiscus Rori; Engel V. Pandey; Chatrien A. L. Sinjal (Jurnal Ilmiah PLATAX, 2020)
Recognize close to Bunaken National Park and largely influenced by the mouth of the Likupang River, having a compact rooting system makes trapped particles suspended in the water column into the sediment. This study aims to determine the spatial distribution of Cadmium metal levels in Mangrove sediments. Sediment samples were taken spatially at point 1 (N 01 ° 40,314 'E 125 ° 04,032') area close to the mainland, point 2 (N 01 ° 40,336 'E 125 ° 03,999') at the center of Mangrove root are present, and point 3 (N 01 ° 40,328 'E 125 ° 03,973') leading to the sea. Sediment samples were analyzed with AAS in the BARISTAND laboratory in Manado with Indonesian National Standards (SNI). The results obtained with the average value in ppm at each point are first point 1, level 0.04, second point, level 5.88, and the third point, level 3.88. The concentration at point second and the third are above the CCME Criteria. This study result at point 2 as the center of concentration of Mangrove roots obtained the highest value, followed at point 3 at a point near the sea and then the lowest at point 1 close to the coast. Keywords: Sediment; Mangrove root; Cadmium ABSTRAKBerada berdekatan dengan TN Bunaken serta besar dipengaruhi oleh muara sungai Likupang, memilki sistem perakaran yang kompak menjadikan terperangkapnya partikel tersuspensi di kolom air menjadi sedimen. Penelitian ini bertujuan untuk mengetahui distribusi spasial kandungan logam Cadmium pada sedimen Mangrove. Sampel sediment diambil secara spatial yaitu titik 1 (N 01°40.314’ E 125°04.032’) yang dekat dengan daratan, titik 2 (N 01°40.336’ E 125°03.999’)pada bagian pusat adanya konsentrasi perakaran, dan titik 3 (N 01°40.328’ E 125°03.973’) berada pada kearah laut.  Sampel sedimen di analsis dengan AAS di laboratorium BARISTAND di Manado dengan standard SNI.  Hasil yang diperoleh dengan nilai rata rata dalam ppm ditiap titik adalah :  titik 1, nilai 0,04, titik 2, nilai 5,88, dan titik 3, nilai 3,88, pada titik 2, dan 3 sudah melebihi baku mutu yang direkomendasikan oleh CCME yaitu 0,7 ppm. Dari penelitian ini disimpukan pada titik 2 sebagai pusat konsentrasinya perakaran Mangrove diperoleh nilai paling tinggi, diikuti pada titik 3 pada titik arah dekat dengan laut kemudian terendah pada titik 1 yang dekat dengan arah pantai.Kata kunci: Sediment; Mangrove root; Cadmium